2014
DOI: 10.1590/1519-6984.21512
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality effect on the allelopathy of cerrado species

Abstract: The Brazilian cerrado presents strong climate seasonality. During the dry season, plants may be exposed to stressful situations, such as a soil surface water deficit, that stimulate their chemical defenses. However, the seasonality effect on the production of allelopathic compounds of cerrado plant species is poorly understood. In this study, the phytotoxic activities of common native cerrado plants were evaluated during rainy and dry seasons. Crude leaves extracts (10% concentration: weight/volume, with dry l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 12 publications
2
17
0
4
Order By: Relevance
“…us, seasonal changes in the water status of Cerrado can be critical to signaling changes in allelochemical synthesis, maximizing the action of allelochemicals on targets. Corroborating our observations, Gatti et al (2014) showed that Cerrado plant species presented the greatest phytotoxic potential with extracts obtained from specimens collected during the dry season. Pinto & Kolb (2016) observed that using extracts from ve Cerrado species obtained from specimens collected after the dry season or during the wet season presented greater phytotoxic e ects, and Murakami et al (2009) showed that extracts from leaf samples did not show variation in allelopathic potential between any of the four seasons.…”
Section: Discussionsupporting
confidence: 84%
“…us, seasonal changes in the water status of Cerrado can be critical to signaling changes in allelochemical synthesis, maximizing the action of allelochemicals on targets. Corroborating our observations, Gatti et al (2014) showed that Cerrado plant species presented the greatest phytotoxic potential with extracts obtained from specimens collected during the dry season. Pinto & Kolb (2016) observed that using extracts from ve Cerrado species obtained from specimens collected after the dry season or during the wet season presented greater phytotoxic e ects, and Murakami et al (2009) showed that extracts from leaf samples did not show variation in allelopathic potential between any of the four seasons.…”
Section: Discussionsupporting
confidence: 84%
“…The ecosystem is the second largest Brazilian domain after the Amazonian (Gatti et al, 2014) and extends over all regions of Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…The reason could be a result of the contained higher concentration of secondary metabolites for the leaves of plants that growths in high latitudes compare with that growth in low latitudes (Wright et al 2004). Gatti et al (2014) also found that climate conditions can affect plant secondary metabolism (such as precipitation and temperature) and then alter the allelopathic activity of plant species via alter the production of allelochemicals. The result may also be attributed in part to the fact that A. retroflexus originated in America (Mandák et al 2011, Yang et al 2011) and/ or south-eastern Asia (Yang et al 2011) which have higher similarity climate conditions as Zhenjiang rather than Jinan.…”
Section: Discussionmentioning
confidence: 95%